Hearing Paul's voice: insights for teaching and preaching - Boring, M. Eugene (William B. Eerdmans Publishing Company, 2020)
"Boring offers a historically informed and pastorally sensitive reading of the Pauline voices in the New Testament for contemporary preachers and teachers"--